The effects of pleural fluid drainage on respiratory function in mechanically ventilated patients after cardiac surgery - Brims, Fraser; Davies, M.; Elia, A.; Griffiths, M. (2015)
BACKGROUND: Pleural effusions occur commonly after cardiac surgery and the effects of drainage on gas exchange in this population are not well established. We examined pulmonary function indices following drainage of pleural effusions in cardiac surgery patients. METHODS: We performed a retrospective study examining the effects of pleural fluid drainage on the lung function indices of patients recovering from cardiac surgery requiring mechanical ventilation for more than 7 days. We specifically analysed patients who had pleural fluid removed via an intercostal tube (ICT: drain group) compared with those of a control group (no effusion, no ICT). RESULTS: In the drain group, 52 ICTs were sited in 45 patients. The mean (SD) volume of fluid drained was 1180 (634) mL. Indices of oxygenation were significantly worse in the drain group compared with controls prior to drainage. The arterial oxygen tension (PaO2)/fractional inspired oxygen (FiO2) (P/F) ratio improved on day 1 after ICT placement (mean (SD), day 0: 31.01 (8.92) vs 37.18 (10.7); p<0.05) and both the P/F ratio and oxygenation index (OI: kPa/cm H2O=PaO2/mean airway pressure×FiO2) demonstrated sustained improvement to day 5 (P/F day 5: 39.85 (12.8); OI day 0: 2.88 (1.10) vs day 5: 4.06 (1.73); both p<0.01). The drain group patients were more likely to have an improved mode of ventilation on day 1 compared with controls (p=0.028). CONCLUSIONS: Pleural effusion after cardiac surgery may impair oxygenation. Drainage of pleural fluid is associated with a rapid and sustained improvement in oxygenation.